A study of as‐grown, poled and reduced Rh‐doped KNbO3 single crystals by high‐resolution X‐ray diffraction, Raman scattering, photoluminescence and dielectric measurements. (1st August 2014) - Bhagavannarayana, G.; Choubey, A.; Kushwaha, S. K.; Sharma, S. N.; Rani, R.; Vijayan, N.
Abstract : As‐grown and chemically reduced Rh‐doped (1500 p.p.m.) KnbO3 single crystals grown by the Czochralski method have been characterized. Reduction of the grown crystals at different levels was carried out under a mixture of CO and CO2 gases as the crystals were grown with excess oxygen. The effect of reduction and poling on crystalline perfection was studied by high‐resolution X‐ray diffraction (HRXRD) using a multi‐crystal X‐ray diffractometer developed in‐house. The diffraction curves of the as‐grown, electrically poled, moderately reduced and heavily reduced single‐crystal specimens show remarkable differences. The studies by HRXRD reveal that poling has some influence on the improvement of crystalline perfection, while chemical reduction has a great influence on crystalline perfection; at moderate reduction the crystal becomes nearly perfect, but when the reduction is very heavy the crystal quality decreases slightly, although it is still better than for unreduced samples. Asymmetry of the diffraction curves with respect to the peak position reveals that the as‐grown specimens contain a high concentration of both vacancies and self‐interstitials. After poling, the concentration of self‐interstitial defects is lowered to some extent. When the specimen is moderately chemically reduced, the scattered intensity on both sides of the peak is greatly reduced, showing that the concentrations of both vacancies and interstitials are reduced to a great extent owing to chemical reduction. This clearly indicates that, as a result of the chemical reduction of oxygen in the crystal, crystalline perfection is enhanced significantly. However, under heavy chemical reduction, the number of vacancy defects is increased to a significant extent. Raman scattering, dielectric and photoluminescence studies also show interesting features, with excellent correlation with the degree of crystalline perfection influenced by the processes of reduction and poling.